ANALISIS INTEGRASI KONTEN KREATIF MEDIA SOSIAL DALAM MODUL AJAR EKONOMI UNTUK MENINGKATKAN KETERLIBATAN BELAJAR SISWA - Syari'ah; Ana Armanita; Dino Ardinal; Fauzan; Feri Naldi; Fresy Chelcilia; M. Syukur; Mitahul Jannah; Muhammad Paisal; Sintia Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the integration of creative social media content in economics teaching modules and its contribution to student learning engagement at the senior high school (SMA) level. Employing a qualitative descriptive approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation of economics teachers and students. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing. The findings reveal that the integration of creative social media content in economics teaching modules is carried out through four primary forms: embedding educational video links via QR codes, utilizing social media infographics as conceptual illustrations, assigning students to produce creative content, and facilitating discussions based on viral content relevant to economic topics. This integration demonstrably enhances student learning engagement across three dimensions: behavioral, emotional, and cognitive engagement, with the strongest effects observed in the emotional and behavioral dimensions. Supporting factors include teachers' digital competence and adequate school infrastructure, while inhibiting factors encompass the potential for digital distraction and inequalities in digital access among students. The findings are analyzed through the theoretical lenses of Constructivism, Social Learning Theory, Student Engagement Theory, Connectivism, and the Cognitive Theory of Multimedia Learning. This study contributes to the development of an economics learning model that is responsive to the digital ecosystem inhabited by Generation Z students.